2018
DOI: 10.1590/1806-9282.64.04.346
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal obesity and reduction of glomerular filtration

Abstract: The objective was to evaluate the association between nutritional status and the glomerular filtration rate (GFR) in remaining quilombolas. Cross-sectional study carried out on 32 remaining quilombola communities in the municipality of Alcântara-MA. The nutritional indicators (IN) used were: body mass index (BMI); Waist circumference (WC); Waist-to-hip ratio (WHR); Waist-to-height ratio (WHtR); conicity index (CI) and estimated visceral adipose tissue (VAT). GFR was estimated from the CKD-EPI creatinine-cystat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
1
2
0
1
Order By: Relevance
“…Dias et al reported that the GFR was decreasing with increasing mean values of nutritional indicators of abdominal obesity regardless of sex. 29 Our study found inverse trends in association between RFM and eGFRcys in females (r s = −.193, P < .0001) and in males (r s = −.114, P = .01).…”
Section: Ta B L Esupporting
confidence: 40%
See 1 more Smart Citation
“…Dias et al reported that the GFR was decreasing with increasing mean values of nutritional indicators of abdominal obesity regardless of sex. 29 Our study found inverse trends in association between RFM and eGFRcys in females (r s = −.193, P < .0001) and in males (r s = −.114, P = .01).…”
Section: Ta B L Esupporting
confidence: 40%
“…The median, interquartile range (IQR) of RFM in females was higher than that in males (44.8 (42.3-47.2) % vs 31.3 (28.8-34.1) %, respectively; P < .0001). The median (IQR) of BMI in females was no higher than that in males (30 (27-34) kg/m 2 vs 30 (27)(28)(29)(30)(31)(32)(33)(34), respectively; P = .5152). The obesity prevalence was 99% in males and 98% in females according to RFM.…”
Section: Re Sultsmentioning
confidence: 85%
“…Так, в нескольких исследованиях продемонстрирована прямая связь АО со сниженной СКФ и патологией Бюллетень сибирской медицины. 2021; 20 (4): 39-48 почек [23][24][25]. Однако А. Shahali и соавт.…”
Section: Discussionunclassified
“…The pattern of body fat distribution is a more significant risk factor in morbid processes than overall obesity, which is characterized by body fat accumulation in the central and peripheral areas of the body. Within this perspective, the accumulation of adipose tissue in the abdominal region, where fat deposits are concentrated in this area, is associated with an exponential increase in morbidity and mortality (16) . The present study identified a reduction in the Hip Circumference (HC)variable (from 112.26 to 101.13 -p = 0.005), but this reduction did not show to be as significant as that observed in the Waist Circumference (WC) variable (from 99.21 to 84.9).…”
Section: Discussionmentioning
confidence: 99%